The Contribution of the Fisheries Sector to Food Security in Indonesia: A Case Study from Bone Regency, South Sulawesi - Anton; Nurayu pratiwi; Fina Fatwa Sari; Toto Hardianto; Suryo Wirawan Anton; Muh.Afif Bafdah (Jurnal Studi Perikanan Berkelanjutan, 2025)
This study aims to analyze the contribution of the fisheries sector in supporting food security among coastal communities in Bone Regency, South Sulawesi. Data were collected from March to June 2025 through a survey involving 150 respondents, consisting of fishers, fish farmers, and fish processing business actors. The research employed both quantitative and qualitative approaches, with data collected through questionnaires, in-depth interviews, and field observations. The analysis was conducted using descriptive quantitative methods, t-tests, and regression analysis to examine differences and factors influencing household food security in fisheries-based communities. The results showed that the fisheries sector made a significant contribution to food security in terms of animal protein availability, fish price affordability, and dietary diversity. The average household fish consumption reached 38 kg per capita per year, which is higher than the national average. The most influential factors affecting food security were household income, education level, and fisheries business diversification. These findings emphasize that the fisheries sector plays a strategic role in achieving sustainable food security in coastal areas